2021
DOI: 10.1186/s12872-021-02277-y
|View full text |Cite
|
Sign up to set email alerts
|

Does overnight duty affect vascular endothelial function?

Abstract: Background The reactive hyperemia index (RHI), which is obtained from the measurement of peripheral arterial tonometry (PAT), is highly associated with the percentage change in the end-diastolic arterial diameter (%flow-mediated dilatation) at reactive hyperemia. Low RHI is reported to be a mortality risk in patients with a high risk of cardiovascular (CV) disease. CV events are thought to be induced by physical and mental stress, including long-term fatigue and lack of sleep. However, the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 52 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…However, none of these five studies addressed the comparison of interest: the effect of napping/sleeping during night shift work (compared to no napping/sleeping) on the non-invasive indicators of endothelial function. We charted the key findings from these five ancillary articles [28,[47][48][49][50], which can be accessed in Appendix B. Below, we describe these studies along with the research gaps.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, none of these five studies addressed the comparison of interest: the effect of napping/sleeping during night shift work (compared to no napping/sleeping) on the non-invasive indicators of endothelial function. We charted the key findings from these five ancillary articles [28,[47][48][49][50], which can be accessed in Appendix B. Below, we describe these studies along with the research gaps.…”
Section: Resultsmentioning
confidence: 99%
“…We identified five unique ancillary studies with a cumulative study sample of n = 110 individuals, of which 87% were shift workers [28,[47][48][49][50]. Amir and colleagues enrolled 30 healthy physicians working at a hospital in Israel [28].…”
Section: Description Of Populations Studiedmentioning
confidence: 99%
See 1 more Smart Citation
“…RHI represents an alternative method to flow-mediated dilatation (FMD), the reference method, since it has the advantage of being simple, operator independent, and therefore less prone to operator bias and variability [36,51]. In addition, RHI has shown a significant correlation (r = 0.55, p < 0.0001) with FMD [52,53] and it is widely used, alone or in combination with FMD and/ or other markers of vascular function, not only for clinical practice but also to study the effect of drugs, supplements, foods and exercise in numerous human interventional trials [54][55][56][57][58]. Regarding the secondary outcomes, a wide range of metabolic and functional markers related to the aging process, and directly and/or indirectly associated to vascular function, has been identified.…”
Section: Plos Onementioning
confidence: 99%
“…This causes blood vessels to tighten, raising blood pressure and possibly developing hypertension [41]. Another study found that intracellular magnesium concentrations and flow-mediated arterial dilation were reduced during prolonged sleep deprivation [42].…”
Section: [23] Amentioning
confidence: 99%